2019
DOI: 10.21203/rs.2.14126/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving the participation of adults with visual and severe or profound intellectual disabilities: A process evaluation of a new intervention

Abstract: Background While the participation of adults with visual and severe or profound intellectual disabilities (VSPID) in society and community life is important, evidence-based interventions for improve their participation are lacking. We conducted a process evaluation of the implementation of ‘Care for Participation+’ (CFP+), a new intervention targeting the attitudes of direct support professionals (DSPs) toward the participation of adults with VSPID, within a residential facility in the Netherlands. Methods CFP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…First, it is possible that CFP+ simply does not induce changes in DSPs’ attitudes towards the participation of adults with VSPID. However, this finding would contradict the results of a previous study, which showed that after training, DSPs worked towards goals of improving self‐management, involvement in existing activities, and developing new roles and activities for the target group (Hanzen et al., 2020). Nevertheless, our finding that DSPs were less focused on the disabilities of adults with VSPID could be understood as the first indication of a changing attitude, which is in line with a previous study (Hanzen et al., 2016).…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…First, it is possible that CFP+ simply does not induce changes in DSPs’ attitudes towards the participation of adults with VSPID. However, this finding would contradict the results of a previous study, which showed that after training, DSPs worked towards goals of improving self‐management, involvement in existing activities, and developing new roles and activities for the target group (Hanzen et al., 2020). Nevertheless, our finding that DSPs were less focused on the disabilities of adults with VSPID could be understood as the first indication of a changing attitude, which is in line with a previous study (Hanzen et al., 2016).…”
Section: Discussioncontrasting
confidence: 71%
“…The demonstrably effective BPRA approach (Korevaar & Dröes, 2016; Swildens et al., 2011), adjusted for adults with VSPID (Hanzen et al., 2016), prompted the development of CFP+. Moreover, drawing on recent work on the definition and operationalization of the concept of participation of adults with VSPID (Hanzen et al., 2017, 2020), we tested CFP+ in a three‐arm trial in which the PMM control group was considered a “low‐dose” CFP+ intervention and the usual care control group served as a reference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations